Korelasi Konflik Kerja Dengan Tingkatan Stres Kerja Pada Perawat Di Rumah Sakit Umum Daerah Petala Bumi Provinsi Riau Tahun 2019 - Trisna Jayati (Sistem Informasi, 2020)
Prolonged stress can have an impact on reducing concentration, nurses become irritable with patients, increase absenteeism, disrupt sleep patterns, and reduce the quality of work by providing nursing care to patients. The purpose of this study was to determine the relationship of work conflict with the level of work stress on nurses at Petala Bumi Regional General Hospital, Riau Province in 2019. The type of research used was observational with analytic cross-sectional study design. The sample in this study was 101 nurses. Data analysis was performed univariate, bivariate and multivariate. The results of bivariate research variables work conflict related to the level of work stress are differences of opinion (p value = 0.002), misunderstanding (p value = 0.004), feeling disadvantaged (p value = 0.004) and feeling sensitive (p value = 0.004). Variables that have a causal relationship with work stress are differences of opinion, misunderstanding, feeling disadvantaged, sensitive feelings. The conclusion in this study is that there is a causal / multivariate relationship between differences of opinion, misunderstanding, feeling disadvantaged, feeling sensitive with an increase in work stress on nurses. It is recommended to the hospital, especially hospital management to take an intensive approach to nurses and supervise so that the source of the difference can be minimized and work that cannot be completed which can lead to disputes that cause stress.